2011
DOI: 10.1021/ac102545e
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Gold Nanoparticles by Field-Flow Fractionation Coupled Online with Light Scattering Detection and Inductively Coupled Plasma Mass Spectrometry

Abstract: An analytical platform coupling asymmetric flow field-flow fractionation (AF(4)) with multiangle light scattering (MALS), dynamic light scattering (DLS), and inductively coupled plasma mass spectrometry (ICPMS) was established and used for separation and quantitative determination of size and mass concentration of nanoparticles (NPs) in aqueous suspension. Mixtures of three polystyrene (PS) NPs between 20 and 100 nm in diameter and mixtures of three gold (Au) NPs between 10 and 60 nm in diameter were separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(113 citation statements)
references
References 29 publications
0
111
2
Order By: Relevance
“…The small gold nanospheres had a very regular shape (Fig. 1), narrow size distribution (2r = 15.6 ± 1.6 nm), and narrow absorption peak (518 nm), while the gold nanoflowers were of irregular shape, larger size, and highly polydisperse (40-120 nm), with an absorption well extended into the NIR region [48,49]. Big regularly shaped gold nanospheres with a hydrodynamic diameter of 86 nm were employed to identify effects that are caused by large particle size.…”
Section: Characterization Of Gold Nanospheres and Gold Nanoflowersmentioning
confidence: 99%
“…The small gold nanospheres had a very regular shape (Fig. 1), narrow size distribution (2r = 15.6 ± 1.6 nm), and narrow absorption peak (518 nm), while the gold nanoflowers were of irregular shape, larger size, and highly polydisperse (40-120 nm), with an absorption well extended into the NIR region [48,49]. Big regularly shaped gold nanospheres with a hydrodynamic diameter of 86 nm were employed to identify effects that are caused by large particle size.…”
Section: Characterization Of Gold Nanospheres and Gold Nanoflowersmentioning
confidence: 99%
“…Alternatively, AuNPs are easily visualized by TEM, and bright-field and dark-field microscopy without the need for a fluorophore, which enables quantitative characterization of the intracellular trafficking steps, and allows for a more thorough understanding of this process [163,174,180].…”
Section: Systemic Administrationmentioning
confidence: 99%
“…The results demonstrated that nanoparticulates at 50-800 nm radius indeed migrate from the nanocomposite but ICP-MS signals corresponding to clay minerals were absent. In a further study, (102) the analytical platform was applied to characterization of Au nanoparticles in the livers of rats, which were dosed with 10 nm, 60 nm, or a mixture of 10 and 60 nm nanoparticles by intravenous injection. The homogenized livers were solubilized in tetramethylammonium hydroxide, and the recovery of Au nanoparticles from the livers amounted to 86-123 % of their total Au content.…”
Section: Spectroscopic Spectrometry Chromatography and Other Technmentioning
confidence: 99%